Acute cell rejection of a kidney transplant in a patient of african origin: clinical observation - M. Sh. Khubutiya; V. O. Aleksandrova; A. G. Balkarov; V. E. Vinogradov; N. V. Zagorodnikova; R. V. Storozhev; N. V. Shmarina; N. V. Borovkova; I. V. Dmitriev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The origin of the recipient is one of the recipient-related factors that statistically significantly affects the outcomes of kidney transplantation, but this factor is not so relevant in our country. The article presents the first experience of kidney transplantation in a patient of African descent at the N.I. N.V. Sklifosovsky.Material and methods. Allogeneic renal graft transplantation from a post-mortem donor was performed in a 60-year-old African male patient with stage 5 chronic kidney disease as a result of hypertensive nephroangiosclerosis.Results. The early postoperative period was complicated by the development of acute cellular graft rejection grade 1a-b according to Banff. Anti-crisis therapy was performed with some positive effect, however, in the late postoperative period, a loss of renal graft function was noted, and the patient was returned to renal replacement therapy with program hemodialysis.Conclusion. Patients of African ancestry are at increased risk of adverse outcomes due to immunological causes and require more careful immunological selection of a donor organ, an enhanced immunosuppressive regimen, and close monitoring after transplantation.